How Do They Get There? An Examination of the Antecedents of Centrality in Team Networks - Klein, Katherine J.; Lim, Beng‐Chong; Saltz, Jessica L.; Mayer, David M. (Academy of Management Journal, 2004)
Drawing on social exchange and similarity-attraction theories, we hypothesized that individuals' demographic characteristics, values, and personality influence their acquisition of central positions in their teams' social networks. Education and neuroticism predicted centrality five months later; individuals who were highly educated and low in neuroticism became high in advice and friendship centrality and low in adversarial centrality. Team members' values similarity to their teammates also predicted advice and friendship centrality; demographic similarity had limited effects.